Should the management of high grade cervical squamous intraepithelial lesion (HSIL) be different in HIV-positive women? - Gilles, Christine (AIDS Res Ther, 2021)
BACKGROUND: This study compares the management and outcome of high grade squamous intraepithelial lesions (HSIL) in HIV-positive and -negative women and identifies risk factors for treatment failure. METHODS: This retrospective, controlled study includes 146 HIV-positive women, matched for HSIL, age and year of diagnosis, with 146 HIV-negative women. Differences were analysed using parametric and non-parametric tests and Kaplan–Meier survival curves. A binary logistic regression was used to assess risk factors for treatment failure. RESULTS: Persistence of cervical disease was observed most frequently in HIV-positive women (42 versus 17%) (p  <  0.001) and the cone biopsy margins were more often invaded in HIV-positive-women than in HIV-negative ones. (37 versus 16%; p  <  0.05). HIV-positive women, with successful cervical treatment had better HIV disease control: with significantly longer periods of undetectable HIV viral loads (VL) (19 versus 5 months; p  <  0.001) and higher CD4 counts (491 versus 320 cells/mm(3); p  <  0.001). HIV-positive women with detectable VL at the time of dysplasia had 3.5 times (95% IC: 1.5–8.3) increased risk of treatment failure. Being treated through ablative therapy was associated with a 7.4, four-fold (95% IC: 3.2–17.3) increased risk of treatment failure compared to conization CONCLUSION: HIV-positive women have a higher risk of treatment failure of HSIL than do HIV-negative women, especially when ablative therapy is used and in women with poor control of their HIV infection. The management and the follow- up of HSIL’s guidelines in this high-risk population should be adapted consequently: for HIV-positive women with uncontrolled viral load, excisional treatment should be the preferred therapy, whereas for women with undetectable viral load, CD4  +  lymphocytes higher than 500 cells/mm(3) and with a desire of pregnancy, ablative therapy may be considered.